Chemical Characterization of Sambucus nigra L. Flowers Aqueous Extract and Its Biological Implications - Pedro Ferreira-Santos; Helder Badim; Ângelo C. Salvador; Armando J. D. Silvestre; Sónia A. O. Santos; Sílvia M. Rocha; Ana M. Sousa; Maria Olívia Pereira; Cristina Pereira Wilson; Cristina M. R. Rocha; José António Teixeira; Cláudia M. Botelho (Biomolecules, 2021)
The main goal of this study was to chemically characterize an aqueous S. nigra flower extract and validate it as a bioactive agent. The elderflower aqueous extraction was performed at different temperatures (50, 70 and 90 °C). The extract obtained at 90 °C exhibited the highest phenolic content and antiradical activity. Therefore, this extract was analyzed by GC-MS and HPLC-MS, which allowed the identification of 46 compounds, being quercetin and chlorogenic acid derivatives representative of 86% of the total of phenolic compounds identified in hydrophilic fraction of the aqueous extract. Naringenin (27.2%) was the major compound present in the lipophilic fraction. The antiproliferative effects of the S. nigra extract were evaluated using the colon cancer cell lines RKO, HCT-116, Caco-2 and the extract’s antigenotoxic potential was evaluated by the Comet assay in RKO cells. The RKO cells were the most susceptible to S. nigra flower extract (IC50 = 1250 µg mL−1). Moreover, the extract showed antimicrobial activity against Gram-positive bacteria, particularly Staphylococcus aureus and S. epidermidis. These results show that S. nigra-based extracts can be an important dietary source of bioactive phenolic compounds that contribute to health-span improving life quality, demonstrating their potential as nutraceutical, functional foods and/or cosmetic components for therapeutic purposes.